Hubungan Physical Literacy terhadap Tingkat Kebugaran Jasmani Siswa Kelas XI SMA Negeri 6 Kota Jambi - Nala Ambarwati; Reza Hadinata; Ceppy Pradana Putra (SPRINTER: Jurnal Ilmu Olahraga, 2026)
This study was designed to identify the physical capacity of eleventh-grade students at SMA Negeri 6 Jambi City and to examine its relationship with their physical fitness levels. A quantitative approach with a correlational design was employed. Purposive sampling was used to select 59 students who met the predetermined criteria. Physical literacy was measured using the Adolescent Physical Literacy Questionnaire (validity 0.680–0.790; reliability α = 0.951), and physical fitness was assessed using the Nusantara Student Fitness Test (TKPN) with a validity of 0.76. Data were analyzed using the Pearson Product Moment correlation test via SPSS version 21. The findings revealed a significant positive relationship between the two variables. Most students fell into the Moderate (34.5%) category for physical literacy and the Sufficient (35.6%) category for physical fitness. A correlation coefficient of r = 0.548 (p = 0.000 < 0.05) confirms that strengthening physical literacy through well-structured and engaging physical education learning can meaningfully contribute to improving students' fitness.